PENINGKAATAN HASIL BELAJAR BIOLOGI MENGGUNAKAN MODEL KOOPERATIF NHT PADA MATERI SISTEM PERNAPASAN DAN EKSRESI KELAS XI IPA.1 SMAN 1 KEPENUHAN ROKAN HULUTAHUN PELAJARAN 2013/2014 - Sumarni Sumarni (JURNAL PENDIDIKAN ROKANIA, 2020)
Activities and learning outcomes of biology students in class XI IPA.1 SMA Negeri 1 Kepenuhan in the 2013/2014 school year was not satisfactory. The method used by the teacher so far has not been able to improve the activities and student learning outcomes in biology. For this reason, efforts are needed to improve the activities and learning outcomes of students in biology by applying cooperative learning models of the NHT type. The purpose of this study was to explain the process of increasing the activities and learning outcomes of biology students on the material of the respiratory system and excretion in class XI IPA.1 SMA Negeri 1 Kepunuhan Rokan Hulu Regency with cooperative learning of the NHT type. This type of research is classroom action research (CAR) on the material of the respiratory system and excretion. The subjects of this study were the students of class XI IPA.1 of SMA Negeri 1 Kepenuhan 2013/2014 Academic Year. This research consists of two cycles, each cycle consisting of planning, implementation, observation and reflection. The research instrument was in the form of student activity observation sheets, teacher activity observation sheets, learning achievement test sheets. Data were analyzed with descriptive statistics to see an increase in student learning activities and outcomes. The results of the study showed that, NHT type cooperative learning can increase student activities which include observing material explanations presented by the teacher, collaborative activities in groups, presentations, submitting activities questions and activities answer questions. Improved student learning outcomes can be seen from the completeness of student learning. The completeness of student learning outcomes in the first cycle was 68.18% in the second cycle increased to 81.82%. The conclusion of this study is the learning of the NHT cooperative model can improve the activities and learning outcomes of students in the biology of the respiratory system and the excretory system in class XI IPA.1 SMA Negeri 1 Kepunuhan.